A Preliminary Investigation of Depression in People with Pathological Dissociation. Issue 5 (19th October 2020) - Fung, Hong Wang; Chan, Chitat; Ross, Colin A.; Choi, Tat Ming
ABSTRACT: Depression is a common and challenging comorbid condition in people with pathological dissociation. To our knowledge, this preliminary study is the first study that has looked at the clinical correlates of depression in a sample of people with pathological dissociation (N = 72). We found that severe depression is common in this sample and that depression is associated with dissociative symptoms, post-traumatic stress disorder (PTSD) symptoms, borderline personality disorder symptoms and clinical recovery; the level of depression is also associated with both childhood and adulthood betrayal trauma but not with childhood and adulthood trauma with less betrayal. PTSD symptoms are the most significant correlates of the level of depression in this sample. Some clinical implications are discussed. Our initial findings imply that it may be important to manage depression by preventing adulthood betrayal trauma and stabilizing PTSD and dissociative symptoms when working with service users with pathological dissociation. Further studies are needed.